Rahasia Keberhasilan Penanaman Gereja Melalui Kepribadian Seorang Hamba - Flesia Nanda Uli Boangmanalu; Mely Triani Sihombing; Melethios Pakpahan; Kallistratos Rumabutar; Megawati Manullang (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
This article is based on the declining awareness of church ministers about what the congregation needs from the church. The lack of God's servants in seeing and feeling the needs of the congregation, so that the congregation has a great opportunity not to grow in quantity and spirituality. The aim of this research is to find out the key to the success of a Servant of God in carrying out church planting. The method used is descriptive qualitative, namely analyzing and concluding various opinions from source books/journals from various experts regarding the secret of the success of the Servant of God in church planting. A church that can meet the needs of its congregation, provides spiritual growth for His congregation and quantity growth for the existence of the church.